BEST ENVIRONMENTAL MANAGEMENT PRACTICE IN THE HOTEL INDUSTRY - Lkhamtseden.B,; Khaliun.B, (Journal of Business and Innovation (Бизнес & Инноваци), 2023)
Even though, we can’t say exactly how many hotels are running all over the world, we can collect the approximate numbers from Booking.com that says it offers 202,842 hotels globally. Imagine they all provide single use items, plastic bottles, plastic straws, and plastic bags which are used only 10 minutes in average. Approximately 15% of single –use plastic is purchased out of habits, and while these products add no value to the guest experience, that have become the expectation. [1] Our research findings indicate that a hotel with 95 guest rooms use 38,700 bottles yearly as complimentary amenity and 19,200 bottles for meeting and events. In total 57,9002 plastic waste is being produced which is possibly replaced with alternative options. After our hotel initiated Accor Hotels Groups’ sustainable program Planet 21, we were instructed to recycle plastic bottles and remove plastic straws. In meantime we are offering less amenities in the rooms which meets people’s basic need of showering and washing face daily. We replaced plastic cup to reusable glass in the restroom and saved 8452$ yearly. A survey of over 80 guests showed that no one found that the project had a negative impact of their stay. [2] But to eliminate all the plastic use throughout the hotel is very challenging, if our customers are not involved. Guests should be communicated through notice boards letter in the rooms saying that how it can help us and what is the advantage of acting together. While we are running sustainable business via implementing Planet 21 program such as reducing as much as plastic we can helps us to strengthen our reputation with in well-known global corporates and increase our occupancy and ADR.